Restrictions on the Freedom of Establishment in the Light of Selected Decisions by the Court of Justice of the European Union - Gadkowski , Tadeusz (Studia Oeconomica Posnaniensia, 2015)
This paper presents the freedom of establishment in the context of the other freedoms in the internal market of the European Union. In particular, the issue of restrictions on the freedom of establishment, as set up in the Treaty of Lisbon and others, will be the subject of a detailed analysis. The author discusses the most relevant judgments by the Court of Justice of the European Union and highlights the most important trends in the case law of the court in this regard.